Violence and civilization in the Western states-systems - Linklater, Andrew (Cambridge University Press, 2016)
"Andrew Linklater's The Problem of Harm in World Politics (Cambridge, 2011) created a new agenda for the sociology of states-systems. Violence and Civilization in the Western States-Systems builds on the author's attempts to combine the process-sociological investigation of civilizing processes and the English School analysis of international society in a higher synthesis. Adopting Martin Wight's comparative approach to states-systems and drawing on the sociological work of Norbert Elias, Linklater asks how modern Europeans came to believe themselves to be more 'civilized' than their medieval forebears. He investigates novel combinations of violence and civilization through a broad historical scope from classical antiquity, Latin Christendom and Renaissance Italy to the post-Second World War era. This book will interest all students with an interdisciplinary commitment to investigating long-term patterns of change in world politics"--Provided by publisher.